Associations between depression, anxiety and medication adherence among patients with arterial hypertension: Comparison between persons exposed and non-exposed to radiation from the Semipalatinsk Nuclear Test Site. (December 2018) - Dyussenova, Lyazzat; Pivina, Lyudmila; Semenova, Yuliya; Bjørklund, Geir; Glushkova, Natalia; Chirumbolo, Salvatore; Belikhina, Tatyana
Abstract: In this study, we investigated the association between depression, anxiety and medication adherence in patients with arterial hypertension living in East Kazakhstan region. The sample size included 795 patients, of whom 403 patients were exposed to radiation at the Semipalatinsk Nuclear Test Site from 1949 to 1989, while 395 patients were unexposed to radiation due to their very remote residence from the Site at the same period. Both exposed and unexposed patients showed no significant differences concerning body mass index, smoking habit, the presence of hypercholesterolemia, and hypertension grade. Patients with arterial hypertension previously exposed to radiation had significantly higher rates of low medication adherence, subclinical and clinical depression, situational anxiety of moderate and severe grade, and personal anxiety of moderate grade. A logistic regression analysis allowed us to identify the presence of significant positive association between medication adherence and anxiety in exposed patients (OR = 4041 (95%CI:1709–9556) p = 0.001) and marginal association (OR = 2998 (95%CI:1008–8915) p = 0.048) between the same parameters in unexposed patients. It might prove to be useful to introduce psychological and medical counseling with an emphasis on strengthening of medication adherence and to inform the local population about radiation effects and dosimetry data. Highlights: The population of Kazakhstan was exposed to radiation due to nuclear weapon testing. Association between radiation exposure and hypertension was established. Radiation exposed patients with hypertension have higher mental distress rates. Depression and anxiety are associated with lower medication adherence.